Peran Sikap sebagai Pemediasi terhadap Pengaruh Persepsi Harga dan Persepsi Kualitas pada Niat Beli (Survei Niat Beli Konsumen pada Kerajinan Kulit di Kabupaten Magetan) - Dian Citaningtyas Ari Kadi (Al Tijarah, 2016)
This study aimed to examine the effect of price perception, perception of quality, and consumer attitudes toward the purchase intention. Samples of this research are tourists visiting Magetan leather industrial district that has purchase intention. The data collection was done by giving a set of questions to the respondent or written questions to be answered (the questionnaire). The scale used is a Likert scale with a range of five options that are used as the measurement instrument that has been collected kuesioner. Data then tested the consistency and precision of the measuring instrument through validity and reliability test. Based on the analysis, this study indicates that the perception of quality and price perception in a positive effect on the formation of consumer attitudes. This indicates that the perception of quality and price is an important variable to consider in influencing consumer attitudes. The results also indicate that the positive effect on consumer attitudes and purchase intent of consumers, so the higher the consumer’s attitude, the higher purchasing intentions.